Discovery of 7-azaindole based anaplastic lymphoma kinase (ALK) inhibitors: Wild type and mutant (L1196M) active compounds with unique binding mode - Gummadi, V.R.; Rajagopalan, S.; Looi, C.Y.; Paydar, M.; Renukappa, G.A.; Ainan, B.R.; Krishnamurthy, N.R.; Panigrahi, S.K.; Mahasweta, K.; Raghuramachandran, S.; Rajappa, M.; Ramanathan, A.; et al. (2013)
We have identified a novel 7-azaindole series of anaplastic lymphoma kinase (ALK) inhibitors. Compounds 7h, 7m and 7n demonstrate excellent potencies in biochemical and cellular assays. X-ray crystal structure of one of the compounds (7k) revealed a unique binding mode with the benzyl group occupying the back pocket, explaining its potency towards ALK and selectivity over tested kinases particularly Aurora-A. This binding mode is in contrast to that of known ALK inhibitors such as Crizotinib and NVP-TAE684 which occupy the ribose binding pocket, close to DFG motif. (C) 2013 Elsevier Ltd. All rights reserved.